PEMBERDAYAAN POKJA IV DESA PONRE-PONRE INOVASI HAIR TONIK DAN SAMPO HERBAL TANAMAN - Damayanti, Wiwi; Muhammad Irfan Taufan Asfar, Andi; Muhamad Iqbal Akbar Asfar, Andi; Srimularahmah, Andi; Ayunita; Ahmad, Susiana; Nurannisa, A. (LPPM UNIVERSITAS LANCANG KUNING, 2023)
Hair is the crown for every person in the world. Some problems that occur on the scalp such as hair loss, dandruff and odor in the hair. Along with the rapid development of the cosmetic and hair care industry which tends to rely on chemicals, synthetics and minoxidil have the potential to cause effects such as skin allergies including hair damage if used for a long time. One of the hair care traditions carried out by our ancestors that has been passed down from generation to generation is the use of coconut milk, which creates an unpleasant or rancid aroma. Therefore, the implementation of community service programs is carried out to be able to help partners by applying the concept of living back to nature which is also supported by the abundance of natural wealth, especially in Ponre-Ponre Village by optimizing the potential of the surrounding nature as Ethno-Hair SPA natural surfactants such as guava leaves. seeds, hibiscus leaves and coconut dregs into hair tonic and shampoo by going through three main stages in implementing this community service, namely socialization/counseling, training and mentoring. The results achieved show that the increase in partners' knowledge regarding the utilization of guava leaves, hibiscus leaves and coconut dregs to become hair tonic and shampoo has increased by 90%, in the ability of partners to utilize guava leaves, hibiscus leaves and coconut dregs reaching 90%.